Evaluation of six phosphorus extraction methods for compliance testing of recycled P fertilizers - Hernandez-Mora, A.; Duboc, O.; Bünemann, E.K.; Ylivainio, K.; Lombi, E.; Symanczik, S.; Horn, D.; Delgado, A.; Abu Zahra, N.; Zuin, L.; Doolette, C.L.; Eigner, H.; et al. (My University, 2025)
Phosphorus (P) recycling for fertilizer production addresses the dependency on phosphate rock and mitigates P losses to the environment. However, predicting plant-available P in recycled fertilizers is challenging due to their diverse chemical composition. This study aimed at identifying the most suitable P extraction method for fertilizer compliance testing, considering their correlation with actual fertilization efficiency, as well as their simplicity, throughput, recognition and cost. Studies on fertilizer P compliance testing often lack recommendations on minimum P extractability threshold values. Here, thresholds are calculated based on actual fertilization efficiency of a large, chemically diverse set of recycled P fertilizers, many of which are already marketed. Thirty recycled P fertilizers were extracted with H2O, neutral ammonium citrate (NAC), electro-ultrafiltration (EUF), ferrihydrite-filled membranes (iron bag; IB), sodium bicarbonate (NaHCO3) and diffusive gradients in thin films (DGT). The mineral replacement value (MRV) of the fertilizer set was previously evaluated in three pot experiments at a fertilization rate of 50 mg kg−1 soil. MRV correlations with the extractions methods showed similar results for all besides H2O, which cannot be a reliable indicator for P availability. Fertilizers were classified as efficient or inefficient based on their MRV exceeding or falling below 60 % of the triple superphosphate reference value. The minimum P extractability threshold value (MPETV) for each method was based on the efficiency classification and it minimized the number of misclassified fertilizers. NAC, with a 60 % extractable minimum P threshold value, was the most adequate method for compliance testing, despite its overestimation of iron phosphate availability.
Keywords: ddc:630